2018
DOI: 10.1017/ice.2018.90
|View full text |Cite
|
Sign up to set email alerts
|

Blood Stream Infection in Patients on Venovenous Extracorporeal Membrane Oxygenation for Respiratory Failure

Abstract: Bloodstream infection (BSI) occurred in 21 of 121 patients (17%) receiving venovenous extracorporeal membrane oxygenation within the median time of 6 days after initiation (interquartile range, 4-19 days). Longer duration of arterial catheterization and more blood transfusions were independently associated with BSI, which is associated with poor clinical outcomes.Infect Control Hosp Epidemiol 2018;1-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 18 publications
1
29
1
Order By: Relevance
“…Previous studies have shown that age, autoimmune comorbidities, higher Sequential Organ Failure Assessment score, and ECMO duration are predictors of NI during ECMO [5,9,21,27]. Contrast to previous studies, we found that decreased BMI and longer CPR to pump on time were associated with NIs in IHCA patients undergoing ECPR.…”
Section: Plos Onecontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that age, autoimmune comorbidities, higher Sequential Organ Failure Assessment score, and ECMO duration are predictors of NI during ECMO [5,9,21,27]. Contrast to previous studies, we found that decreased BMI and longer CPR to pump on time were associated with NIs in IHCA patients undergoing ECPR.…”
Section: Plos Onecontrasting
confidence: 99%
“…ECMO in ECPR (75 [IQR 48-140] hours) is shorter than that of veno-venous ECMO in our previous study (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) days) [9,24].…”
Section: Plos Onementioning
confidence: 76%
See 1 more Smart Citation
“…Although limited by small sample sizes, the incidence of BSI ranged between 13% and 27%. [16][17][18][19][20][21] BSIs are known to be associated with increased mortality in critically ill patients. UTIs and CAUTIs are also frequently encountered HAIs; however, these infections were uncommonly encountered in the ECMO population compared to BSI and VAP.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly it is likely the magnitude of the problem is not fully appreciated: CRIs may be under-reported in the absence of a consensus definition[15] and thus this complication may be under-recognised in clinical practice and less reliably reported in the evidence base. Patients on ECMO generally have multiple invasive lines in addition to the large-bore ECMO lines which increases the number of entry portals for intraluminal contaminants and constitutes an increased risk for BSI among other factors[6, 33]. Routine changeout of ECMO lines is unfeasible due to the high risk of life-threatening complications and patient cardiorespiratory instability precludes this as an option when potential or proven infections occur.…”
Section: Discussionmentioning
confidence: 99%